Development of Lung Ventilator for the Treatment of COVID-19 Patient in Indonesia - Fadilah, Putra Adnan; Prayoga, Febriyan Prayoga; M, M Triprabowo (INSTEP Network, 2021)
Development program of local ventilator component, respiratory flow meter (RFM), respiratory blower fan (RBF), and positive end expiratory pressure (PEEP) valve are the main part of contribution to support medical team during COVID-19 virus outbreak that start on March, 2020 in Indonesia. In the COVID-19 pandemic era ventilator become necessary thing to treat Covid patient especially for worst cases patient. With increasing in people who infected by COVID-19 around the world and also in Indonesia, caused the demand of the ventilator system also increased significantly. In Indonesia many research institution and universities have been initiated to develop the emergency ventilator to support the increasing demand. Some companies in Indonesia initiate to develop the component of the lung ventilator to support other research institution therefore to minimize dependency from import product which is in the pandemic era the component such as flow meter and blower fan is difficult to get caused by stock limitation. In this paper we expose the process on development of three essential component part of the lung ventilator, i.e., respiratory flow meter (RFM), respiratory blower fan (RBF), and positive end expiratory pressure (PEEP) valve. The development of these components is using a standard design procedure and utilized with some design software for obtaining the optimum design result.